DIFFERENT YET CAPABLE: THE ABILITY OF PHYSICALLYCHALLENGED STUDENT SHOWN IN PETANQUE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 21 March 2016 - Having had cerebral palsy since 16, a USM student is unperturbed by the challenge ahead of him and was able to win the medals when given the chance to represent USM in petanque competitions.